Distinct UV–Visible Responsivity Enhancement of GaAs Photodetectors via Monolithic Integration of Antireflective Nanopillar Structure and UV Absorbing IGZO Layer. Issue 13 (15th April 2022) - Liao, Yikai; Zheng, Yixiong; Shin, Sang‐Ho; Zhao, Zhi‐Jun; An, Shu; Seo, Jung‐Hun; Jeong, Jun‐Ho; Kim, Munho
Abstract: Broadband ultraviolet–visible photodetection has been attracting growing research interests in fields of environment, energy, and imaging. Considering the suitable bandgap and high absorption coefficient, GaAs is one of the best candidates for ultraviolet–visible photodetection. In this work, a monolithic integration strategy of nanopillar antireflective structure and InGaZnO (IGZO) ultraviolet absorbing layer is proposed to enhance the ultraviolet–visible spectral responsivity of GaAs photodetectors. Both nanopillar topography and IGZO layer exhibit antireflective performance, leading to the enhancement of the light absorption and responsivity of the photodetectors. By the combination of nanopillar structure and IGZO layer, a distinct responsivity enhancement of more than one‐order magnitude covering 300–800 nm wavelength range is realized compared with planar GaAs photodetectors. This work offers great promises for advanced GaAs‐based ultraviolet–visible optoelectronics. Abstract : In this study, a facile integration scheme is presented to construct an InGaZnO (IGZO)/GaAs heterostructure on GaAs nanopillar array. The IGZO/GaAs nanopillar heterostructure shows outstanding ultraviolet–visible light absorption capability. The IGZO/GaAs photodetector based on the nanopillar topology shows more than one‐order magnitude enhancement in responsivity compared to the device made on planar GaAs surface.